Tracing the History of Tun Sri Lanang in Samalanga Bireuen, Aceh: The Intersection of Arabic Language Science, Management, and Communication - Fatahillah; Nurbaiti; Yusfriadi; Taufiqurrahman, Maulia; Zuriyatina; Emeera (Institute of Education and Social Research, 2023)
This article documents archaeological research on the historical site of Tun Sri Lanang in Samalanga District, Bireuen Regency. The research aims to excavate and understand the historical heritage associated with an important figure in local history. Excavation methods and artifact analysis were used to reveal the historical aspects associated with this site, accompanied by interview methods. This activity illustrates the efforts to trace the history of Tun Sri Lanang by using the approach of Arabic linguistics to understand texts and historical sources, the application of management principles in the management and preservation of historical sites, and communication strategies to promote and increase public awareness of the historical and cultural value of the site.